2017
DOI: 10.18203/issn.2454-5929.ijohns20173030
|View full text |Cite
|
Sign up to set email alerts
|

Current trends of adenotonsillar hypertrophy presentation in a developing country, Nigeria

Abstract: <p class="abstract"><strong>Background:</strong> Adenotonsillar hypertrophy is a common paediatric disorder in Otorhinolaryngological practice worldwide. The prevalence, clinical manifestations and predisposing factors are well documented in developed countries. However, available data shows differences between the various studies. There is paucity of data from developing countries. <span lang="EN-IN">Thus, this study is aimed at assessing the age group distribution, predisposing factor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 8 publications
(8 reference statements)
7
8
0
Order By: Relevance
“…Preschool age, (1 -5) years group were predominant in this study more than another age group this may be due to a higher incidence of upper respiratory tract infection and higher activities of lymphoid tissue at the entrance of upper aerodigestive tract. These findings are similar to another study on the pathology of pediatric tonsils [27].…”
Section: Discussionsupporting
confidence: 92%
“…Preschool age, (1 -5) years group were predominant in this study more than another age group this may be due to a higher incidence of upper respiratory tract infection and higher activities of lymphoid tissue at the entrance of upper aerodigestive tract. These findings are similar to another study on the pathology of pediatric tonsils [27].…”
Section: Discussionsupporting
confidence: 92%
“…Major diagnoses in this study were obstructive sleep apnea, recurrent tonsillitis, and otitis media. Other studies also reported similar findings in their studies 12…”
Section: Discussionsupporting
confidence: 83%
“…Injuries and infections rate is more common in males than in females. This may be due to male is more active and prone to injuries and infections as reported in other studies 12. As illustrated in this study, adenotonsillar surgeries are performed in all sociodemographic strata.…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…Majority of our study population (55.4%) were males and werre between the ages of 2 and 7years. A similar study by Adegbiji et al [ 11 ] from Nigeria also reported study population between 0 and 8 years. ATH is usually seen in children between 2 and 6 years of age and the process of lymphoid involution especially of adenoid may start after this age.…”
Section: Discussionsupporting
confidence: 53%